The radical right, the labour movement and the competition for the workers' vote. (February 2019) - Mosimann, Nadja; Rennwald, Line; Zimmermann, Adrian
This article analyses the capacity of radical right parties to attract support from union members in recent elections in Western Europe. It is argued that unionized voters resist the appeals of the radical right better than non-union members. Using data from the European Social Survey 2010–2016, the article shows that union members are overall less likely to vote for the radical right than non-union members. Even though it is found that unionized working-class and middle-class voters are less likely to vote radical right than their non-unionized peers in the pooled sample, it is also observed that these subgroups of unionized voters and especially unionized working-class voters are not immune to radical right voting in all the countries analysed. The article thus indicates a growing capacity of the radical right to attract unionized working-class segments of the electorate in some countries and to directly compete with left parties for these voters.